Why not talk about repression? Radical Activism and its Responses to Repression - Ellefsen, Rune (PARTECIPAZIONE E CONFLITTO, 2021)
By exploring silence as a response to repression, this study contributes to the literature on the dynamic rela-tionship between protest and repression; it examines the ways in which certain radical activists responded with silence to the escalating repression they were experiencing. Analysis explains how and why they remained si-lent, and the consequences of that silence for individual activists and collective mobilization. Based on a case study of the Stop Huntingdon Animal Cruelty (SHAC) campaign in the UK, this article includes the reflections of activists who experienced repression first-hand. By analysing in-depth interviews and other qualitative data, the study identifies four different forms of silence among the activists facing repression: silence as a strategy, si-lence as a cultural trait, silence due to over-confidence and silence resulting from the normalization of repres-sion. The results show how cultural and strategic dynamics play out in protestors’ experiences of and responses to repression. The study demonstrates the importance of the neglected research area of the response to re-pression for advancing our understanding of the conditions under which repression leads either to demobiliza-tion or to mobilization.